Assessing polytechnic program objectives after two decades: Development and validation of a qualitative evaluation instrument - Noor, Noaryanti Mohd; Ani, Adi Irfan Che; Abdullah, Normah binti; Zin, Rabeah Md; Chohan, Afaq Hayder (International Journal of Innovative Research and Scientific Studies, 2025)
This study presents the development and validation of a structured interview instrument designed to evaluate the long-term effectiveness of Malaysian Polytechnic programs after two decades of implementation. The instrument aims to assess key program outcomes, including employability, skills acquisition, graduate satisfaction, community engagement, and program improvement. A panel of six experts evaluated the instrument using the Content Validity Index (CVI) and Content Validity Ratio (CVR) to ensure item clarity, relevance, and construct alignment. Findings indicated that the majority of items attained excellent content validity, with I-CVI scores of 1.00 for 19 out of 24 items, reflecting unanimous agreement among experts. These included demographic questions and items related to job relevance, skills development, and program improvement. However, several items failed to meet the minimum I-CVI threshold of 0.78, signaling the need for revision or exclusion. Despite this, the overall instrument demonstrated acceptable scale-level validity, with an S-CVI/Ave of 0.82 and an S-CVI/UA of 0.79. The results affirm the potential of the instrument as a reliable tool for assessing polytechnic program outcomes and underscore the value of expert involvement in the instrument development process. The study contributes to the field of educational assessment by offering a validated framework for program evaluation that can support evidence-based improvements in technical and vocational education policy and practice.